COLLABORATION MOTIVATES INCREASED EMPLOYEE PERFORMANCE - Ansar; Antong; Muammar; Syafruddin, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The Regional Secretariat of East Luwu Regency, in improving employee performance in supporting services and dynamic changing conditions, requires improving employee performance. Teamwork and work motivation are important factors that influence employee performance. The Regional Secretariat of East Luwu Regency faces challenges in improving employee performance, where teamwork and work motivation are key elements that need to be considered. This research aims to analyse the effect of collaboration on employee performance through work motivation of East Luwu Regency Regional Secretariat Employees. This research uses a quantitative approach, with the population being 109 East Luwu Regency Regional Secretariat Employees, with a sampling technique using saturated sampling. Data was collected through questionnaires distributed to employees of the East Luwu Regency Regional Secretariat. The data analysis technique used was descriptive verification using the SmartPLS statistical tool. The research results show that collaboration has a positive and significant effect on employee performance and motivation. Motivation has a direct impact on employee performance and is also able to mediate the relationship between cooperation and performance significantly. Good collaboration increases employee motivation. This high motivation then encourages employees to work harder, be more creative, and be more committed to their work, which ultimately improves performance.